Surreal and Canny Selves: Photographic Figures in Claude Cahun - Gayle Zachmann (Studies in 20th & 21st Century Literature, 2003)
In her 1975 essay, Le Rire de la méduse, Hélène Cixous enthusiastically announced that it was high time for women to enter into discourse. A full half-century earlier, Claude Cahun (1894-1954), a powerful writer and a haunting photographer and artist, was already inscribing herself, Woman, and a woman's voice in visual and verbal self-portraits, photomontages, prose texts, poetry, and aesthetic and political treatises. Cahun's uncanny interventions in both verbal and visual discourse cannily interrogate conventions of literary and pictorial representation and the constructions of self, gender and culture that they exhibit. Insistently asking readers and spectators, "What's wrong with this picture?," her carnivalesque play with the doxa and the politics of identity, destabilizes not only gender and genre norms, but the boundaries and distinctions between visual and verbal representation. Surreal and Canny Selves explores the aesthetic frameworks of writer/artist Claude Cahun. Elucidating how Cahun's questioning of her self and Surrealist representations of woman were part of a much more expansive adventure that questioned more than femininity—the manuscript moves on to trace how and what Cahun's foregrounding of figuration and, more specifically, photographic figuration, might signify for the uncanny aesthetic practices deployed in the hybrid text Aveux non avenus.
Keywords: Le Rire de la méduse; Hélène Cixous; women; discourse; Claude Cahun; writer; photographer; Woman; woman& #x27; s voice; visual; verbal self-portraits; photomontages; prose texts; poetry; aesthetic; political treatises; treatises; uncanny; verbal; self; gender; culture; representation; carnivalesque; politics of identity; identity; gender norms; genre norms; Surreal and Canny Selves; Surrealist representations of woman; surrealist; surrealism; femininity; Aveux non avenus; carnival